Antimicrobial sensing coupled with cell membrane remodeling mediates antibiotic resistance and virulence in enterococcus faecalis (2020)
Bacteria have developed several evolutionary strategies to protect their cell membranes (CMs) from the attack of antibiotics and antimicrobial peptides (AMPs) produced by the innate immune system, including remodeling of phospholipid content and localization. Multidrug-resistant Enterococcus faecalis, an opportunistic human pathogen, evolves resistance to the lipopeptide daptomycin and AMPs by diverting the antibiotic away from critical septal targets using CM anionic phospholipid redistribution. The LiaFSR stress response system regulates this CM remodeling via the LiaR response regulator by a previously unknown mechanism. Here, we characterize a LiaR-regulated protein, LiaX, that senses daptomycin or AMPs and triggers protective CM remodeling. LiaX is surface exposed, and in daptomycin-resistant clinical strains, both LiaX and the N-terminal domain alone are released into the extracellular milieu. The N-terminal domain of LiaX binds daptomycin and AMPs (such as human LL-37) and functions as an extracellular sentinel that activates the cell envelope stress response. The C-terminal domain of LiaX plays a role in inhibiting the LiaFSR system, and when this domain is absent, it leads to activation of anionic phospholipid redistribution. Strains that exhibit LiaX-mediated CM remodeling and AMP resistance show enhanced virulence in the Caenorhabditis elegans model, an effect that is abolished in animals lacking an innate immune pathway crucial for producing AMPs. In conclusion, we report a mechanism of antibiotic and AMP resistance that couples bacterial stress sensing to major changes in CM architecture, ultimately also affecting host–pathogen interactions.